Exploring the biochemical and productivity implications of incorporating mustard cake in Hypsizygus ulmarius (Bull.) cultivation - Rautela, Indra; Kalia, Sonika; Chaudhary, Prashant Kumar; Tiwari, Monika; Purohit, Jagdish C; Kumar, Rajan; Anthwal, Riyanka; Rajput, Sudhanshu; Choudhary, Rashmi (Plant Science Today, 2024)
The study aimed to evaluate the biological efficiency and nutritional composition of Hypsizygus ulmarius (Bull.), an edible and medicinal mushroom species often overlooked by Indian farmers. The mushrooms were cultivated on wheat husk as the control substrate from October to February. The substrate was enriched with mustard cake (M) at concentrations of 10 % (M500), 20 % (M1000) and 30 % (M1500) by dry weight to assess the impact on yield. The growth parameters, including the size and weight of fruiting bodies from each type of substrate were recorded. The control substrate, consisting of wheat straw alone, required the shortest period for mycelium growth at 33.125 ± 0.99 days, while wheat straw supplemented with 30 % mustard cake (M1500) took the longest time at 46.6 ± 1.5 days. However, the M1000 substrate (20 % mustard cake) had the shortest time span for pin head formation, taking 46 ± 1.41days and for maturation to fully grown fruiting bodies, requiring 50.25 ± 2.12 days. The M1000 substrate also produced the highest yield of 5533.2 kg with the greatest biological efficiency of 92.2 %, but comparatively least values were obtained in M1500, with a yield of 2088.28 kg and a biological efficiency of 51.28 %. The highest total carbohydrate content was found in M500 (10 % mustard cake), at 71.91 %, along with a fiber content of 13.19 %. The highest protein (38.06 %) and fats (2.73 %) contents were observed in M1500. The results of this study suggest that mustard cake can be used as an effective supplement to enhance the nutritional content, biological efficiency and productivity of Hypsizygus ulmarius.